Management Strategies of Agricultural Production Units to Deal with Ecological Changes of Urmia Lake (Case Study: Azar Shahr) - Neda Ghodrati; Azhdar Karami; fatemeh Kazemiyeh; Adel Dabbagh Mohammadi Nassab (Journal of Agricultural Science and Sustainable Production, 2018)
Climate change and global warming has caused environmental problems in many areas of the world. The critical situations of Urmia Lake resulted from these factors, also improper management of human and natural resources, Therefore, had a significant impact on agricultural business. If the farmers don’t have the capacity for dealing with the risks posed by climate change, irreparable damages to the agriculture sector will be entered. So identify management strategies in the agricultural division to deal with the threats and eliminate weaknesses and strengthen the system and opportunities is essential. This research in the Azar-Shahr region as one of the important agricultural areas in East Azarbaijan province, In order to identify the strengths and weaknesses, opportunities and threats, as internal and  external environment of agricultural production unit in the face of ecological changes in Lake Urmia was carried out. This research in terms of goal is applied and methodology is Descriptive and analytical. The statistical society will comprise experts in the field of agriculture and the status of the Urmia Lake with sufficient knowledge and experience. Reagard to select the samples, non-probability and purposive method was used. Targeted selecting of samples as snowball sampling method was utilized. In this study, the SWOT model was used to analyze strengths, weaknesses, opportunities and threats, and IEF and EFE matrix formation and development of strategies was conducted. Based on the results, management strategies, and so proper and compatible patterns with the ecological and climatic condition were determined.